2-Arachidonoylglycerol endocannabinoid signaling coupled to metabotropic glutamate receptor type-5 modulates anxiety-like behavior in the rat ventromedial prefrontal cortex. (June 2017) - Almeida-Santos, Ana F; Moreira, Fabricio A; Guimaraes, Francisco S; Aguiar, Daniele C
2-Arachidonoylglycerol and anandamide are the main endocannabinoids, which act through cannabinoid type-1 and type-2 receptors. Among its many functions, anandamide modulates anxiety-like behaviors in the ventromedial prefrontal cortex. The role of 2-arachidonoylglycerol in this region, however, has remained unclear. Here, we verified whether intra- ventromedial prefrontal cortex injection of 2-arachidonoylglycerol or URB602, a monoacylglycerol lipase inhibitor (responsible for 2-arachidonoylglycerol hydrolysis), induce anxiolytic-like effects in Wistar rats. Since activation of metabotropic glutamate receptor type 5 promotes diacylglycerol lipase-α-mediated 2-arachidonoylglycerol synthesis, we also verified if the blockade of this receptor impairs the anxiolytic-like effect induced by URB 602. 2-Arachidonoylglycerol reduced anxiety-like response in rats exposed to the Elevated Plus Maze test, an effect mimicked by URB602. Cannabinoid type-1 and type-2 receptor antagonists prevented these effects. The pre-treatment with an ineffective dose of MPEP, a metabotropic glutamate receptor type 5 antagonist, also attenuated the anxiolytic-like effect of URB602. Moreover, immunofluorescence microscopy revealed co-expression of metabotropic glutamate receptor type 5 and diacylglycerol lipase-α in several neurons in slices from the ventromedial prefrontal cortex. Altogether, our results implicate 2-arachidonoylglycerol and both cannabinoid receptors on anxiety-related behaviors mediated by ventromedial prefrontal cortex. Further, these data support a role for the coupling between metabotropic glutamate receptor type 5 activation and 2-arachidonoylglycerol signalling as a mechanism modulating aversive responses.